A Review of International Experience for Telerehabilitation of Post-stroke Patients with Aphasia and Cognitive Problems - Aksana N. Mazilina; Anatoliy V. Skalny; Anatoliy D. Fesyun; Maxim Yu. Yakovlev; Sergey A. Savko; Evegeniya D. Namiot (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
Stroke remains one of the most common reasons of disabilities worldwide. Aphasia, memory and cognitive problems are among common stroke consequences significantly reducing stroke survivors' life quality. To grant access of a large number of stroke survivors to rehabilitation services, and sustain continuous rehabilitation during pandemic, the telerehabilitation can be used. This article summarizes current approaches on telerehabilitation of post-stroke patients with aphasia, cognitive and memory problems. Authors made a search of research articles and review papers from international medical journals indexed in Scopus, Sciencedirect, and PubMed databases. The results show that the telerehabilitation is feasible providing significant clinical outcomes and can be organized synchronously and asynchronously to meet needs for increasing demand of post-stroke patients. Despite the positive effects of telerehabilitation, there were some limitations. To overcome these limitations, further clinical studies on large groups are needed.